Assessing junior doctors’ preparedness in inpatient cardiac arrest management: a cross-sectional study at a university hospital - Muhammad Azmi Bin Sukor; Dazlin Masdiana binti Sabardin (BMC Medical Education)
Abstract Background Cardiac arrest is an emergency that requires immediate and effective intervention. Junior doctors, who are often the first responders, play an important role in the initial management of in-hospital cardiac arrest (IHCA). However, there are still concerns about their preparedness in managing this critical event. Thus, this study aimed to evaluate the knowledge, attitude, and confidence level to manage IHCA among junior doctors in a tertiary university hospital. Methodology A cross-sectional study using a self-administered validated questionnaire covering demographics, knowledge, attitude, and confidence related to CPR over one year from August 2023 to December 2024 involving 115 junior doctors. Data were analyzed using Statistical Package for Social Science (SPSS) version 29. Descriptive statistics were used to characterize the study population, and Spearman’s correlation was used to assess the relationships between knowledge, attitude, and confidence scores. Results The median age was 27 years (IQR 26,28) with 50 (43.5%) males and 65 (56.5%) females. Most had completed BLS training (N = 104, 90.4%) and nearly all(N = 110,95.7%) had prior CPR experience, with 56.5% having performed CPR within the past month. The median knowledge score was 77.77% (IQR 72.22%, 83.33%). Knowledge gaps were identified in airway adjunct use (22.6% correct) and bag-mask ventilation selection (36.5% correct). Attitudes toward CPR were generally positive, with 98.2% (N = 113) believing CPR could save lives. However, 40% (N = 46) expressed concern about unintentionally causing patient harm and legal implications when initiating CPR. Confidence was highest in basic CPR tasks: chest compressions (N = 112, 97.4%) and bag-mask ventilation (N = 108, 94.0%). However, lower confidence was noted for advanced skills such as defibrillation (N = 87, 75.7%) and drug administration (N = 91, 79.1%). A significant positive correlation was found between knowledge-attitude (ρ = 0.272, p = 0.003) and attitude-confidence (ρ = 0.552, p < 0.001). The knowledge-confidence correlation was weak and not statistically significant (ρ = 0.180, p = 0.054). Conclusion The knowledge of CPR among junior doctors in HCTM was found to be adequate. However, concerns and insecurities in managing cardiac arrest were still observed. Additional training and simulations are recommended to address this issue. Clinical trial number not applicable.